Assessing The Relationship Between Brand Image, Intellectual Capital, Human Capital, And Public Relation Strategy And Firm Value (International Forum of Researchers and Lecturers, 2023)
This study aims to examine the intricate relationship among brand image, intellectual capital, human capital, public relation strategy, and firm value. The research adopts a qualitative approach utilizing semi-structured interviews with key stakeholders from diverse industries. A purposive sampling technique is employed to select participants with relevant expertise. Data analysis involves thematic analysis to identify patterns, themes, and relationships among the variables. The findings reveal nuanced interconnections between brand image, intellectual and human capital, public relation strategies, and firm value, highlighting the importance of holistic management approaches in enhancing organizational performance and competitiveness.